Comparative Characterization of Lung Muscarinic Receptor Binding After Intratracheal Administration of Tiotropium, Ipratropium, and Glycopyrrolate - Masaki Ogoda; Ryo Niiya; Tadatsura Koshika; Shizuo Yamada (Elsevier, 2011)
The aim of the current study was to characterize comparatively the binding of muscarinic receptor in the lung of rats intratracheally administered anticholinergic agents (tiotropium, ipratropium, glycopyrrolate) used clinically to treat chronic obstructive pulmonary disease (COPD) and asthma. Binding parameters of [N-methyl-3H]scopolamine methyl chloride ([3H]NMS) were determined in tissues (lung, bladder, submaxillary gland) of rats intratracheally administered tiotropium, ipratropium, and glycopyrrolate. The in vitro binding affinity of tiotropium for the receptors was 10 - 11-fold higher than those of ipratropium and glycopyrrolate. Intratracheal administration of tiotropium (0.6 - 6.4 nmol/kg) caused sustained (lasting at least 24 h) increase in the apparent dissociation constant (Kd) for [3H]NMS binding in rat lung compared with the control value. Concomitantly, there was a long-lasting decrease in the maximal number of binding sites (Bmax) for [3H]NMS. Similary, ipratropium and glycopyrrolate at 7.3 and 7.5 nmol/kg, respectively, brought about a significant increase in Kd for [3H]NMS binding. The effect by ipratropium was observed at 2 h but not 12 h, and that by glycopyrrolate lasted for 24 h. Both agents had little influence on the muscarinic receptors in the bladder and submaxillary gland. The present study provides the first evidence that tiotropium, ipratropium, and glycopyrrolate administered intratracheally in rats selectively bound muscarinic receptors of the lung, and tiotropium and glycopyrrolate had a much longer-lasting effect than ipratropium. Keywords:: chronic obstructive pulmonary disease, tiotropium, ipratropium, glycopyrrolate, ex vivo lung muscarinic receptor binding